Multiple breath washout in pediatric patients after lung transplantation. Issue 1 (21st August 2017) - Nyilas, S.; Carlens, J.; Price, T.; Singer, F.; Müller, C.; Hansen, G.; Warnecke, G.; Latzin, P.; Schwerk, N.
Abstract : Forced expiratory volume in 1 second (FEV1 ) from spirometry is the most commonly used parameter to detect early allograft dysfunction after lung transplantation (LTx). There are concerns regarding its sensitivity. Nitrogen‐multiple breath washout (N2 ‐MBW) is sensitive at detecting early global (lung clearance index [LCI]) and acinar (Sacin ) airway inhomogeneity. We investigated whether N2 ‐MBW indices indicate small airways pathology after LTx in children with stable spirometry. Thirty‐seven children without bronchiolitis obliterans syndrome [BOS] at a median of 1.6 (0.6‐3.0) years after LTx underwent N2 ‐MBW and spirometry, 28 of those on 2 occasions (≤6 months apart) during clinically stable periods. Additional longitudinal data (11 and 8 measurements, respectively) are provided from 2 patients with BOS. In patients without BOS, LCI and Sacin were significantly elevated compared with healthy controls. LCI was abnormal at the 2 test occasions in 81% and 71% of patients, respectively, compared with 30% and 39% of patients with abnormal FEV1 /forced vital capacity (FVC). Correlations of LCI with FEV1 /FVC ( r = 0.1, P = .4) and FEV1 ( r = −0.1, P = .6) were poor. N2 ‐MBW represents a sensitive and reproducible tool for the early detection of airways pathology in stable transplant recipients. Moreover, indices were highly elevated in both patients with BOS. Spirometry and LCI showed poor correlation, indicating distinct and complementary physiologic measures. Abstract : The authors advocate a greater role for nitrogen multiple breath washout as a diagnostic tool in monitoring pediatric patients after lung transplantation.